Enhancing Financial Literacy of Rural MSMEs through Service Learning: Daily Cash Recording Training - Jusuf Satriani; Mohammad Ja’far As-Shodiq As-Shodiq; Citra Alissya Yustisianti; Rhendica Rhendica (Kerigan: Jurnal Pengabdian Masyarakat, 2024)
Purpose: Micro, Small, and Medium Enterprises (MSMEs) play an important role in strengthening the rural economy; however, many MSME operators still face limitations in managing financial administration. The lack of systematic financial records makes it difficult for business owners to evaluate performance and access financial support. This community service activity aims to improve financial literacy and basic financial recording skills among MSME operators in Talang 1 Village through direct education. Method: The activity employed a Service Learning (SL) approach that integrates student learning with community engagement. The implementation stages included preliminary observation, identification of community needs, preparation of training materials, and the delivery of a seminar entitled “The Importance of Financial Recording for Micro Enterprises.” The materials were presented using a participatory and practical approach, supported by case studies and simple daily cash-recording worksheets. Practical Applications: The seminar involved 15 local MSME operators who had not previously received similar training. Participants gained knowledge of basic financial recording, income and expense tracking, and strategies for separating personal and business finances. The participants showed strong enthusiasm and expressed willingness to apply financial recording practices independently. Conclusion: This activity demonstrates that context-based financial education can effectively improve financial literacy among rural MSME actors and support better business governance.